Accounting standard changes and foreign analyst behavior: Evidence from China - Yutao Wang; Yu Hou; Xiaolin Chen (China Journal of Accounting Research, 2012)
This study investigates changes in foreign analyst behavior before and after Chinese New Accounting Standards was implemented during 2007. The empirical results show that after the new accounting standards were implemented, forecast error among foreign analysts decreased in both absolute and relative terms in comparison with domestic analysts, and foreign analysts forecast earnings more frequently than they did before the new accounting standards. These results imply that the implementation of new accounting standards in the Chinese capital market helped mitigate both information asymmetry between listed firms in China and foreign investors, and the 'home bias' of foreign analysts. It also increased the attractiveness of listed firms and facilitated international communication and cooperation. This study also has significant implications for how resource allocation efficiency in the Chinese capital market can be raised and how the 'introducing in' policy should be assessed.
Keywords: G14; G20; M41; 650; New accounting standards; Analyst forecasts; Forecast error